Dilema Digitalisasi: Dampak Positif dan Negatif dari Pelaksanaan Lelang Online - Gilza Azzahra Lukman; Avif Prasetyo; Esmeralda Magdalena; Ummi Maskanah (Universitas Djuanda, 2025)
Online auctions have become one of the most popular transaction mechanisms in the digital era, offering various conveniences and innovations in the world of commerce. This study aims to analyze the positive and negative impacts of online auctions from a socio-legal perspective, encompassing legal, social, and technological aspects. Data collection was conducted through a literature review technique. The results of the study indicate that online auctions provide numerous benefits, such as cost and time efficiency, ease of access, information transparency, and a wider reach for auction participants. These advantages position online auctions as an innovative solution to meet the digital transaction needs of modern society. On the other hand, the study also identifies several challenges, including legal ambiguities due to the proliferation of auction platforms that do not comply with regulatory provisions, risks of price manipulation, fraud, and violations of participants' privacy.